IBM: CRAFTSMAN COMMUNITIES OF VIRGIN COCONUT OIL (VCO) IN SIKO VILLAGE KAYOA SUB-REGENCY NORTH MALUKU PROVINCE - Liestianty, Deasy; Sundari, Sundari; Mas’ud, Abdu (Universitas Islam Negeri Alauddin Makassar, 2018)
Science and Technology Program for the community through coaching and assisting transfer of coconut processing simply technology into quality and durable VCO. IBM Results Program shows that: 1) socialization of coconut processing into VCO oil has been carried out to the community of Siko Kayoa Village in August 2014, 2) Siko Village Community especially the partners in this program have understood and receive technology transfer of making VCO as well as giving a positive response to this program, 3)Response of partner group showed that 100% of the respondents stated VCO socialization and training techniques were very clear and easily understood by the respondents, 99% stated tools and materials was easy to get, 98% of respondents stated the procedure for making VCO was easy, cheap and simple. 100% of respondents are willing to develop VCO making techniques in Siko village. Targets of this program have been achieved 95% by producing outputs skills of the Siko community to process VCO oil and VCO products produced.